Thermal deposition method for p–n patterning of carbon nanotube sheets for planar-type thermoelectric generator. Issue 20 (13th May 2021) - Yamaguchi, Ryohei; Ishii, Taiki; Matsumoto, Masamichi; Borah, Angana; Tanaka, Naoki; Oda, Kaito; Tomita, Motohiro; Watanabe, Takanobu; Fujigaya, Tsuyohiko
Abstract : Thermal deposition of n-dopant onto SWCNT sheet (p-type) using patterned mask can fabricate p–n patterns with high special resolution. Thermoelectric generator using patterned SWCNT sheets exhibited power density of 60 nW cm −2 at Δ T = 25 °C. Abstract : Thermoelectric generators (TEGs) using flexible single-walled carbon nanotube (SWCNT) sheets have a high Seebeck coefficient, remarkable electrical conductivity, and good flexibility, making them promising for the realization of wearable electronics. TEGs with a planar structure are preferable to those with π-shaped structures, as the planar surface enables the device to be attached flat to a surface such as skin. To realize a planar configuration, sequentially repeating p- and n-type areas must be fabricated with high precision. However, there is considerable molecular diffusion in the lateral directions when using solution doping methods, which decreases the patterning resolution. Therefore, in this study, a dry patterning process is developed based on thermal vapor deposition using patterned masks. For the patterning, p-type SWCNT sheets are doped using 2-(2-methoxyphenyl)-1, 3-dimethyl-1 H -benzoimidazol-3-ium iodide as the n-type dopant. The 50 μm-thick SWCNT sheets are doped from the top to the bottom of the sheet with a lateral diffusion of only ∼100 μm. Planar SWCNT-based TEGs with four p–n units exhibit an efficient power generation of 60 nW cm −2 (at Δ T = 25 °C), with scope for further optimization via simulation-based design.